Menopausal hormone therapy: oncological risks - Ekaterina V. Musina; Igor Yu. Kogan (IP Berlin A.V., 2020)
The review article presents an analysis of the literature over the past 10 years on the relationship of menopausal hormone therapy and the risks of developing malignant diseases in women, including risk factors, such as mutations in the BRCA1/2 genes. The main limiting factor in the appointment of menopausal hormone therapy today remains the question: is there a connection between MHT and the development of oncological pathology, due to the high mortality rates from malignant neoplasms, which occupy the 2nd place after cardiovascular diseases. The main localization of the tumor process, which stops the appointment of MHT, is breast cancer. In the structure of the incidence of malignant neoplasms among the female population in Russia, breast cancer occupies a leading place, and this is the main interest in the effect of MHT. The results of large-scale studies are rather ambiguous and do not answer all the questions. Do not forget about other localizations of the tumor process, which MHT can also influence, and about which, there is also no unequivocal answer to the question about the relationship of MHT and the risks of tumor development. As for any therapy, for MHT there are contraindications, which are also covered in the article. The main modes of taking menopausal hormone therapy and their relationship with the risks of tumor development are also presented. The influence of the main components of menopausal hormone therapy on the processes of neoplastic transformation.